Embolization strategies for intracranial dural arteriovenous fistulas with an isolated sinus: a single-center experience in 20 patients. (3rd June 2021) - Hendriks, Eef J; Lynch, Jeremy; Swaminathan, Saravana Kumar; Nicholson, Patrick; Agid, Ronit; Radovanovic, Ivan; Pereira, Vitor M; terBrugge, Karel; Krings, Timo
Abstract : Background: Intracranial dural arteriovenous fistulas (DAVFs) draining into an isolated sinus segment constitute a specific entity within the spectrum of cranial dural AV shunts, with under-reporting of their optimal treatment. Objective: To describe the multimodal treatment approach to isolated sinus DAVFs in a large single-center cohort. Methods: Retrospective analysis of adult patients with an isolated sinus DAVF treated at our institution between 2004 and 2020 was performed. Cases were analyzed for demographics, clinical presentation, angiographic findings, treatment techniques, angiographic and clinical outcomes, and complications. Results: Of 317 patients with DAVFs, 20 (6.3%) with an isolated sinus DAVF underwent treatment. Transarterial embolization was performed through the middle meningeal artery in 9 of 12 procedures, with a success rate of 66.7%. Transarterial glue embolization proved successful in two of five procedures (40%) and Onyx in six of seven procedures (85.7%). Transvenous embolization (TVE) with navigation via the occlusion into the isolated sinus was successful in seven out of nine procedures (77.8%). All three open TVE and one pure open surgical procedure gained complete closure of the fistula. There were two major complications. Complete occlusion of the fistula was eventually obtained in all cases (100%). Conclusions: Isolated sinus DAVFs are always aggressive and require a multimodal approach to guarantee closure of the shunt. Transarterial treatment with Onyx achieves good results. Transvenous treatment appears equally successful, navigating into the occluded segment across the occlusion or via burr hole as backup.